Caring Behavior in Nursing at Majalaya Regional General Hospital - Situmorang, Roganda; Pritama, Julham; Miraj Darajat, Agus (Program Studi Keperawatan Universitas Muhammadiyah Tasikmalaya, 2025)
Nurses providing nursing services are the largest health workforce and services in health services. The results of the situation study informed that nursing services at Majalaya Regional Hospital still found patients complaining about a lack of caring nursing services and a lack of caring leadership management for nurses. The aim of this research is to explore caring behavior in nursing services at the Majalaya Regional General Hospital. The research method uses a mixed methods sequential exploratory strategy. Primary data collection uses data collection techniques by means of in-depth interviews distributing questionnaires. The research sample used a purposive sampling technique, conducted in-depth interviews with 7 nurses and 6 patients and distributed questionnaires to 30 nurses and 30 patients. Data were analyzed using thematic analysis (collaizi's 7-step) and univariate data analysis to calculate frequency data distribution. The research results include caring leadership, caring behavior of nurses and caring services to patients. Health services (nursing) require the synergy of 3 aspects of the role, namely the caring leadership style of the head of the room in managing nurses continuously in the caring behavior of nurses towards recipients of caring services (patients). There is a need to strengthen caring aspects for nurse leaders and nurses in the form of training and regular observation, monitoring and evaluation of the implementation of caring in nursing services.